Analisis Pengaruh Rasio Keuangan dan Ukuran Perusahaan terhadap Nilai Perusahaan - Mettakalyani Gunawan; Fung Jin Tjhai (Media Bisnis, 2025)
The purpose of this study is to obtain empirical evidence regarding the influence of independent variables of dividend policy, investment decisions, firm size, leverage, profitability, activity, liquidity, and sales growth on the dependent variable of firm value. In this study, the population used was manufacturing companies listed on the Indonesia Stock Exchange from 2021 to 2023 using the purposive sampling method. The data obtained were 132 sample data from manufacturing companies for the period 2021 to 2023. The test conducted in this study was multiple regression to determine whether there was an influence between the independent variables on the dependent variable. The results of this study indicate that the variables leverage, profitability, activity, and liquidity have an effect on firm value. Meanwhile, the variables dividend policy, investment decisions, firm size, and sales growth do not affect firm value.